Influence of Socio-demographic Factors on Health Facility-based Childbirth in Yambio County, South Sudan. A Cross-Sectional Study. - Ngbadurezere , William (Student's Journal of Health Research Africa, 2022)
Background: South Sudan is facing a very big challenge with making Maternal Care Services available for women in rural areas due to a lack of sufficient policy for strengthening the health sector in the Country. It’s found out that, most women in South Sudan give birth to their babies on the floor in government hospitals, cutting the umbilical cord with a stick. The study aims to look at the Influence of socio-demographic factors on health facility-based childbirth in Yambio County, South Sudan. Methodology: This was a cross-sectional study using a mixed methods approach to assess factors that influence health facility-based childbirth. This study was conducted from August 2021 to September 2021 among lactating women using Yambio State Hospital for health facility-based childbirth and those residing in Yambio town Payam, Western Equatoria State, South Sudan. Results: (50.3%) of the respondents aged 21-25 years old, the majority of the respondents only completed a primary level of education (46%), followed by those with secondary (32%) and with tertiary education (22%). (82%) were married. The majority (36.8%) of the respondent was unemployed followed by those self-employed (26.8%). Nearly three-quarters (73%) of the respondents did indicate that they had monthly incomes of less than 10,000 SSP. About 23% of respondents had an income of (10,000 SSP – 20,000 SSP) and only about 4% had an income of more than 20,000 SSP. Conclusion: The socio-demographic factors associated with health facility-based childbirth include the mother’s age (21 – 25 years), being a full-time student, and working for either government or private business. Recommendations Women and their husbands should have a source of income so that they would be able to have transport that expectant mothers can easily take to the hospital.